2011
DOI: 10.1111/j.1600-0854.2011.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of VAMP7/TI‐VAMP in Cell Polarity and Lysosomal Exocytosis in vivo

Abstract: VAMP7 or tetanus neurotoxin-insensitive vesicleassociated membrane protein (TI-VAMP) has been proposed to regulate apical transport in polarized epithelial cells, axonal transport in neurons and lysosomal exocytosis. To investigate the function of VAMP7 in vivo, we generated VAMP7 knockout mice. Here, we show that VAMP7 knockout mice are indistinguishable from control mice and display a similar localization of apical proteins in the kidney and small intestine and a similar localization of axonal proteins in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Previous experiments in cultured neurons used silencing approaches and expression of the Longin as dominant-negative fragment to conclude that TI-VAMP was involved in neurite growth. Based on the present data and Sato et al (2011), it is likely that the abovementionedcompensatorymechanismsoccurpreferentiallywhenTI-VAMP is deleted early in development. We conclude that TI-VAMP functions during development in vivo are either dispensable or compensated for by other SNAREs allowing the KO mice to fulfill major developmental processes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous experiments in cultured neurons used silencing approaches and expression of the Longin as dominant-negative fragment to conclude that TI-VAMP was involved in neurite growth. Based on the present data and Sato et al (2011), it is likely that the abovementionedcompensatorymechanismsoccurpreferentiallywhenTI-VAMP is deleted early in development. We conclude that TI-VAMP functions during development in vivo are either dispensable or compensated for by other SNAREs allowing the KO mice to fulfill major developmental processes.…”
Section: Discussionmentioning
confidence: 97%
“…We did not find any defect in growth of TI-VAMP KO cultured neurons in presence or absence of feeding astrocytes. Using hippocampal neurons from a different TI-VAMP KO mouse, Sato et al (2011) reported a modest effect on axonal growth of neurons grown for 3 DIV. Therefore, we are led to the idea that one or several other v-SNAREs or other mechanisms compensate for TI-VAMP functions.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, VAMP7 KO MEFs show phenotypes clearly related to the traffic of lipids and proteins known to reside in membrane domains. While these phenotypic traits do not preclude cell and organism life, 55,56 they may nevertheless induce profound signaling defects 20 which largely remain to explore. Further studies are required to address the impact of this mechanism in the organism and also how a v-SNARE which primarily mediates membrane fusion may also be required at earlier stages of membrane traffic like sorting of some components of membrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were fixed using perfusion with 4% (w/v) PFA in 0.1 M phosphate buffer (pH 7.4) and processed as previously described (Harada et al, 1990, Sato et al, 2011. We performed hematoxylin-eosin staining using standard histological procedures.…”
Section: Histology and Western Blot Analysesmentioning
confidence: 99%
“…We performed hematoxylin-eosin staining using standard histological procedures. Western blot analyses were performed as previously described (Sato et al, 2011) and 10 mg of protein was loaded per lane.…”
Section: Histology and Western Blot Analysesmentioning
confidence: 99%